If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -1x = 5 Reorder the terms: -1x + 4y = 5 Solving -1x + 4y = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -1x + 4y + -4y = 5 + -4y Combine like terms: 4y + -4y = 0 -1x + 0 = 5 + -4y -1x = 5 + -4y Divide each side by '-1'. x = -5 + 4y Simplifying x = -5 + 4y
| 3x+3+x=45 | | -22-5x=-77 | | f(x)=6x+15 | | 8=-2x+5+4x | | 3-y=12 | | 8g+7=119 | | 30=-10x-70 | | 7(x-1)=2x+65 | | 15x+5y=175 | | x+19+2x=-12-2x-19 | | -7-x=-1-2x | | -3+x/6=6 | | -77=-22-5x | | 8x-0.33y=16 | | 7(f+2)=8+5f | | X+19+3x=-26-3x-32 | | 2=-3+x/8 | | n+3.5=7.10 | | 7x-8=78 | | 2x+3=4x+6-(2x+3) | | (234)/(456)*2= | | 5x+6*3x-18=122 | | 1-4(h-1)= | | -4n-8+2n= | | 4m-10=m+11 | | 8-97=25 | | y-3=-1(x-2) | | -2x=1-(-13) | | -6x+15=-3x+30 | | 7x+4x+13=4+2x | | x+9y-13=12 | | 14x-19-6x-5=128 |